Alcohol Excise Duties Burden in the Baltic Countries - Trasberg, Viktor (Estonian Discussions on Economic Policy, 2020)
The paper comparatively analyses the burden of alcohol excise duties for various levels of income earners in the Baltic countries. Understanding the specific allocation of excise duties across consumer groups is a prerequisite for the efficient design of alcohol policies and taxation strategies. Alcohol excise duties have an impact on alcohol prices, and therefore the social behaviour of individuals and consumption structure in general. Alcohol excise duties are considered to be regressive over incomes. This paper provides a comparative assessment of the relative distribution of the excise tax burden across consumers in the Baltic countries. A correlation analyses and Kakwani indexes are used to measure the regressive characteristics of alcohol excise duties. The statistical analyses are conducted on the basis of a consumer survey carried out in all three Baltic countries in 2015 and 2016.